Estimación del área de influencia de árboles dominantes en un bosque de Pinus sylvestris L. - Sierralta L.; Gracia C.A. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The ability of a tree to use the resources of its nearest environment and as consequence of it, its ability to modify the state of those resources, is clearly related to the tree size. Such ability is expressed as the space that surrounds the tree in question. The first difficulty when attempting to quantify the area of influence of a tree appears when trying to establish the parameters that define it. This study presents three empirical approaches, from which the 'area of influence' of the dominating trees in a P. sylvestris stand may be inferred, for an area of the Aragonese Pyrenees. It is an attempt to verify the hypothesis of the existence of a resource availability gradient, from the dominating tree towards its peripheral area. The information gathered by the three approaches may be useful as an efficient management tool to define, for each species of a site, the reach of the area of influence for any individual tree type of a stand.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)